Application of ESI FT-ICR MS to Study Kraft Lignin Modification by the Exoenzymes of the White Rot Basidiomycete Fungus TrametesHirsutaLE-BIN 072 - Moiseenko, Konstantin V.; Savinova, Olga S.; Glazunova, Olga A.; Sinitsyn, Arkadiy P.; Fedorova, Tatiana V. (KnE Life Sciences, 2022)
Trameteshirsuta is a wood rotting fungus that possesses a vast array of lignin degrading enzymes, including7 laccases, 7 ligninolyticmanganese peroxidases, 9 lignin peroxidases and 2 versatile peroxidases. In this study,electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT-ICR MS)was used to examine kraft lignin modification by the enzymatic system of this fungus.The observed pattern of lignin modification suggested that before the 6th day of cultivation,the fungal enzymatic system tended to degrade more oxidized moleculesand, hence, less recalcitrant molecules, with the production of hard-to-modify reduced molecular species. At some point after the 6th day of cultivation,the fungal enzymatic system tended to degrade more oxidized moleculesand, hence, less recalcitrant molecules, with the production of hard-to-modify reduced molecular species. At some point after the 6th day of cultivation,the fungus started to degrade less oxidized, more recalcitrant, compounds, converting them into the more oxidized forms. The altered pattern of lignin modification enabled changes in the fungal enzymatic system. These changes were further attributed to the appearance of the particular ligninolyticmanganese peroxides enzyme(MnP7), which was added by the fungus to the mixture of enzymes that had already been secreted (VP2 and MnP5). Keywords: wood rotting fungi, kraft lignin, mass spectrometry, peroxidases